(untitled) (Research, Society and Development, 2021)
Introduction: External cervical resorption (ECR) is a physiological or pathological event usually detected on radiographic examination, since there are no symptoms in its initial and intermediate phases. Objectives: This case is an important finding because the early detection of this lesion allowed an effective multidisciplinary approach to be carried out. Case Report: Radiography was taken in a 55-year-old male and revealed a radiolucent area on the distal surface of the permanent mandibular left first molar, suggesting ECR with impaired pulpal vitality. Based on the clinical and radiographic examinations, a multidisciplinary approach was established involving endodontic treatment, periodontal surgery and indirect restoration that provided an option for preserve the affected tooth. The early diagnosis of ECR was essential for the successful treatment in order to maintain the satisfactory function for five-year follow-up. Conclusion: Despite the procedures performed, the idiopathic etiology of the lesion contributed to the appearance of recurrences; however, monitoring and maintenance of the affected tooth proved to be important for the longevity of the treatment.